Developing an evaluation framework for selecting optimal medical devices - Juhyeok Park; Eungdo Kim; Kwangsoo Shin (Journal of Open Innovation: Technology, Market, and Complexity, 2019)
The objective of this study is to summarize the current general evaluation process that stakeholders use to evaluate single or multiple medical devices to select the optimal medical device. This study constructed a novel evaluation framework to select the optimal medical device by overcoming the limitations of assessments that were previously confined to the medical device cycle and the purpose of the specific assessment. It also presents a general framework for incorporating usability evaluations into the frame to reflect the objectives and characteristics of key stakeholders in the medical device industry. In addition, the results of medical device evaluation are further analyzed using the analytical hierarchy process (AHP).
Keywords: 650; AHP; economic evaluation; evaluation framework; selecting optimal medical devices; technological evaluation; usability evaluation